(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
University of Chittagong (CU) is well known for its beautiful green campus. It had 11 student halls (plus two were under construction), of which three were ladies’ halls named (Shamsun Nahar, Pritilata and Deshnetri Begum Khaleda Zia). But, due to lack of a proper waste management plan, wastes were found to be scattered in open areas of ladies’ halls premises. So, to protect the environmental quality of three ladies’ halls a research work has conducted during June 2012 to March 2013. Here researcher try to determine the waste generation rates, their physical composition and characterized them. At that time data about disposed wastes were collected weekly from kitchen, dining, canteen, bathroom, and halls premises at 8.00 to 11.00 am and wastes were measured by using weighing machine in kilogram (kg). Based on sources, wastes were categorized mainly on four types, such as: (1) kitchen waste, (2) dining and canteen wastes, (3) bathroom waste, and (4) others (veranda, corridor, and in and around the halls’ campus) wastes. Overall, 18,505.0 kg wastes were disposed from different sources and among them 10,406.0 kg (i.e., 56.24%) were from kitchen, 1,218.5 kg (i.e., 6.59 %) from dining and canteen, 1,570.5 kg (i.e., 8.49 %) from bathroom and 5,310.0 kg (i.e., 28.68 %) from others sources. On an average each student of 3 ladies’ halls disposed 0.029 kg waste per day that gave a total of 8.520 kg wastes during the 10 months of study period. The campus of The University of Chittagong is well known as a habitat of different types of wild animals. So, monthly waste dumping sites were visited and the wild animals those were seen eating foods from dumping wastes were identified with the help of field guides (Section e.g., Grimmett et al., 2009; Ahmed et al., 2009).